Reasons for non compliance of license holders towards disclosure-based regulation in Malaysian securities - Yeon, Asmah Laili (2011)
The objective of this paper is to report the findings of a study amongst licence holders of the capital markets in Malaysia in relation to the implementation of the Disclosure Based Regulation in Malaysia.This survey was conducted among 107 principal and representative licensees registered with the Securities Commission of Malaysia.They consist of licensed dealers, investment advisers and fund managers.The majority of the respondents were capital markets and services representative licensees (CMSRL), while only 17 respondents were capital markets and services licensees.The survey indicates that non compliance occurs because of lack of ethical values and orientation of the players in the industry.In addition, non compliance was also reported to occur due to lack of understanding of law and regulations, inefficient company's surveillance, control and internal monitoring programmes, and weaknesses in the implementation and enforcement of law.Other reasons include greed (wanting to be rich quickly), selective application of the law, complicity between offenders and regulators, slow judicial process, and high legal cost for victims to pursue compensation.As the enforcement agency, Securities Commission should further enhance efforts to monitor and enforce the law of capital markets.On the other hand, the courts have to impose fines on criminals based on the extent of the losses investors have suffered by investors and on the effects of the crime on market stability.More importantly, ethics training should be carried out to license holders by the relevant bodies and agencies in the securities market.This paper provides useful information in relation to factors contributing to non compliance of participants of the capital markets.The enforcement body can implement measures on how to curb the unethical behaviour by carrying out ethics training and introducing new rules and regulations for the industry.